Co-occurring indicator pathogens for SARS-CoV-2: A review with emphasis on exposure rates and treatment technologies. (December 2021) - Khan, Afzal Husain; Abutaleb, Ahmed; Khan, Nadeem A.; El Din Mahmoud, Alaa; Khursheed, Anwar; Kumar, Manish
Abstract: Scientific advancements from 2002 to 2020 for coronaviruses, i.e., SARS-CoV and MERS-CoV outbreaks, could lead towards a better understanding of the exposure to a health crisis. However, data on its transmission routes and persistence in the environment is still in need of the hour. In this review, we discuss the impact of environmental matrices on dealing with the consequences of the global COVID-19 outbreak. We have compiled the most recent data on the epidemiology and pathogenesis of the diseases. The review aims to help researchers and the larger public recognize and deal with the consequences of co-occurring viral indicators for COVID-19 and provide nano-technological perspectives of possible diagnostic and treatment tools for further studies. The review highlights environmental wastes such as hospital wastewater effluents, pathogen-laden waste, pathogen-laden ground/surface water, wastewater sludge residues and discusses their potential remediation technologies, i.e., pathogen-contaminated soil disposal, municipal and medical solid waste collection, recycling, and final disposal. Finally, holistic suggestions to tackle environmental-related issues by the scientific community have been provided, where scientists, consultants may involve in a tiered assessment from the hazard to risk management in the post-COVID-19 world.